Emerging Immunotherapies in Lung Cancer: The Latest Advances and the Future of mRNA Vaccines - Raquel Ramos; Nuno Vale (Vaccines)
Lung cancer is the most lethal malignancy worldwide, having the highest incidence rate. This is a heterogeneous disease classified according to its histological and molecular characteristics. Depending on these, different therapeutic approaches have already been approved for lung cancer treatment targeting genetic alterations or even the immune system. Nonetheless, other therapies are being studied to continuously improve the care and survival of lung cancer patients. Among them, immunotherapies are one of the main targets of investigation to try and combat the ability of some malignant cells to evade anti-tumor responses mediated by the immune system. Cancer vaccine development has emerged as a promising approach to strengthen the patient’s immune system and combat the disease, especially mRNA vaccines. Currently, there are several ongoing studies investigating the therapeutic efficacy of mRNA vaccines in lung cancer treatment alone or combined with other therapeutic drugs. This review aims to highlight the importance of immunotherapy in lung cancer treatment, presenting the most recent advances particularly in mRNA-based vaccines as well as the challenges and future perspectives.